Sclerostin Antibody Treatment Stimulates Bone Formation to Normalize Bone Mass in Male Down Syndrome Mice. (29th December 2017) - Williams, Diarra K; Parham, Sean G; Schryver, Eric; Akel, Nisreen S; Shelton, R Shane; Webber, Jessica; Swain, Francis L; Schmidt, Jami; Suva, Larry J; Gaddy, Dana
ABSTRACT: Down syndrome (DS), characterized by trisomy of human chromosome 21, is associated with a variety of endocrine disorders as well as profound skeletal abnormalities. The low bone mass phenotype in DS is defined by low bone turnover due to decreased osteoclast and osteoblast activity, decreasing the utility of antiresorptive agents in people with DS. Sclerostin antibody (SclAb) is a therapeutic candidate currently being evaluated as a bone anabolic agent. Scl, the product of the sclerostin gene ( SOST ), inhibits bone formation through its inhibition of Wnt signaling. SclAb increases bone mass by suppressing the action of the endogenous inhibitor of bone formation, Scl. To examine the effects of SclAb on the DS bone phenotype, 8‐week‐old male wild‐type (WT) andTs65Dn DS mice were treated with 4 weekly iv injections of 100 mg/kg SclAb. Dual‐energy X‐ray absorptiometry (DXA), microCT, and dynamic histomorphometry analyses revealed that SclAb had a significant anabolic effect on both age‐matched WT littermate controls and Ts65Dn DS mice that was osteoblast mediated, without significant changes in osteoclast parameters. SclAb treatment significantly increased both cortical and trabecular bone mass at multiple sites; SclAb treatment resulted in the normalization of Ts65Dn bone mineral density (BMD) to WT levels in the proximal tibia, distal femur, and whole body. Ex vivo bone marrow cultures demonstrated that SclAb increased the recruitment of the mesenchymal progenitors into the osteoblast lineage, as indicated by increased alkaline phosphatase–positive colonies, with no effect on osteoclast differentiation. Together, in the setting of a murine model of DS and decreased bone turnover, SclAb had a potent anabolic effect. SclAb stimulated bone formation and increased osteoblastogenesis without affecting osteoclastogenesis or bone resorption. These data suggest that SclAb is a promising new therapy to improve bone mass and reduce fracture risk in the face of the low bone mass and turnover prevalent in the DS population. © 2017 The Authors JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.